2022
DOI: 10.3390/biomedicines10010128
|View full text |Cite
|
Sign up to set email alerts
|

HDL Is Not Dead Yet

Abstract: High-density lipoprotein cholesterol (HDL-C) levels are inversely correlated with coronary heart disease (CHD) in multiple epidemiological studies, but whether HDL is causal or merely associated with CHD is unclear. Recent trials for HDL-raising drugs were either not effective in reducing CHD events or, if beneficial in reducing CHD events, were not conclusive as the findings could be attributed to the drugs’ LDL-reducing activity. Furthermore, the first large Mendelian randomization study did not causally rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 108 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…[10][11][12][13] However, recent genetic and clinical trial data suggest that the simple quantity of HDL-C may not be causal in preventing atherosclerosis nor reflect HDL functionality. 14 Many authors have observed that the functional activity of HDL in plasma samples from patients with cardiovascular disease may be substantially lower than predictions based on HDL-C or APOA1 levels [15][16][17][18][19] and the term "dysfunctional HDL" describes the phenomenon. Notably, HDL particles from cardiovascular disease patients are enriched in proteins involved in the acute-phase response, such as members of the SAA (serum amyloid A) family.…”
Section: See Accompanying Editorial On Page 870mentioning
confidence: 99%
“…[10][11][12][13] However, recent genetic and clinical trial data suggest that the simple quantity of HDL-C may not be causal in preventing atherosclerosis nor reflect HDL functionality. 14 Many authors have observed that the functional activity of HDL in plasma samples from patients with cardiovascular disease may be substantially lower than predictions based on HDL-C or APOA1 levels [15][16][17][18][19] and the term "dysfunctional HDL" describes the phenomenon. Notably, HDL particles from cardiovascular disease patients are enriched in proteins involved in the acute-phase response, such as members of the SAA (serum amyloid A) family.…”
Section: See Accompanying Editorial On Page 870mentioning
confidence: 99%
“…Thus, P. gingivalis LPS has a potential role in inducing macrophages to modify native LDL [ 171 ]. Likewise, P. gingivalis can initiate the oxidation of high-density lipoprotein (HDL), reverse the cholesterol transport pathway, remove cholesterol from macrophages, and thus contribute to atherosclerosis [ 172 , 173 ]. In addition, it can lead to an imbalance of proatherogenic and atheroprotective cytokines by disturbing the balance of Th17 and Treg [ 174 ].…”
Section: Clinical Implication Of Periodontal Infections Caused By ...mentioning
confidence: 99%
“…One of the problems with HDL particle analysis for diagnostic purposes has been the extreme complexity of these particles and the lack of resolution of older measurement tools. For example, although high HDL-cholesterol (HDL-C) concentrations have been found to be protective against CVD, several large recent studies demonstrated that the relationship between HDL-C concentration and adverse health outcomes tends to follow a U-shaped curve, with both low HDL-C and very high HDL-C being associated with increased cardiovascular (CV) events (21)(22)(23). Clearly, it is not simply the measurement of the total amount of cholesterol carried within HDL that is diagnostic, but rather some other aspect of HDL that is critical, whether it be compositional, structural, or functional.…”
Section: Hdl Glycosylation Profiling For Diagnostic Purposesmentioning
confidence: 99%